Worldwide Daily Optimum Tilt Angle Model to Obtain Maximum Solar Energy. Issue 1 (2nd January 2023) - Modarresi, Javad; Hosseinnia, Hamed
Abstract : This paper aims to obtain the overall equations of the yearly, seasonal, monthly and daily optimum tilt angles worldwide. So, the daily optimum tilt angle variations are examined for 337 locations in the northern hemisphere and 247 locations in the southern hemisphere, and it is shown that the daily optimum tilt angle changes in cosine form over a year. Then, the daily optimum tilt angle is estimated using a cosine function. The daily optimum tilt angle is independent of the longitude and can be estimated using a function that depends on the latitude and the number of days. The resulting model can be used to calculate the optimum tilt angles in desired intervals. In order to verify the validity of the results, the results of the proposed model are compared with the results of the other papers. It is shown that the presented model can calculate the optimum tilt angles with acceptable accuracy in the southern and northern hemispheres.